Similar serological response to conventional therapy for syphilis among HIV-positive and HIV-negative women. Issue 5 (October 1995) - Goeman, J; Kivuvu, M; Nzila, N; Behets, F; Edidi, B; Gnaore, E; Van Dyck, E; St Louis, M; Piot, P; Laga, M
Abstract : OBJECTIVES--To compare characteristics of syphilis serological reactivity in HIV positive (+) and HIV negative (-) female sex workers, as well as the serological response to therapy after treatment with intramuscular benzathine penicillin, 2.4 million U weekly, for three consecutive weeks. METHODS--Rapid plasma reagin (RPR) and Treponema pallidum haemagglutination assay (TPHA) results of 72 HIV-positive and 121 HIV-negative women reactive in both tests were assessed. The response to therapy was prospectively monitored with quantitative RPR serology in 47 HIV-positive and 73 HIV-negative patients. Cumulative probabilities of becoming nonreactive by RPR were compared at six months, one and two years after therapy. RESULTS--At enrolment, the geometric mean titres of RPR and TPHA were lower in HIV-positive patients (RPR, 1:2.6) than in HIV-negative patients (RPR, 1:3.8; p < 0.01). The evolution over time of RPR titres was similar among HIV-positive patients as compared to HIV-negative patients. Among patients with an initial RPR titre of < 1:8, 53% of HIV-positive and 44% of HIV-negative patients became RPR negative two years after therapy. Among patients with an RPR titre of 1:8 or greater at enrolment, 83% of HIV-positive and 90% of HIV-negative patients had reached at least a fourfold decline of RPR titres two years after therapy. CONCLUSIONS--Syphilis serology findings (both RPR and TPHA) may be altered in the presence of HIV infection, but the serological response to therapy was similar in HIV-positive and HIV-negative patients.